Topological Electronic Transition Contributing to Improved Thermoelectric Performance in p-Type Mg3Sb2- xBix Solid Solutions - Xie, Sen (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.